The effect of psychological stress on the menstrual cycle among medical students - Mayasah Abdul Elah Sadiqi; Alaa Ali Salih (Journal of the Pakistan Medical Association, 2024)
Objectives: To assess the prevalence of menstrual abnormalities among medical students, and to explore its association with stress levels. Method: The cross-sectional study was conducted from May 18 to May 28, 2021, in Baghdad, Iraq, after approval from the ethics review committee of the College of Medicine, Mustansiriyah University, Baghdad, and comprised female medical students in Baghdad. Data was collected using simple random sampling technique and employed an online questionnaire that was distributed through e-mail. The questionnaire had 3 domains: demographic and anthropometric data, menstrual history, and psychological stress. The psychosocial stress levels was assessed using the Perceived Stress Scale-10. Data was analysed using SPSS 25. Results: There were 397 subjects with mean age 20.84±1.621 years (range: 17-24 years). Mean age of menarche was 12.65±1.399 years, mean body mass index was 22.71±6.369kg/m2 and the mean stress score was 22.71±6.016. Dysmenorrhea was seen in 369(92.9%) cases, and premenstrual symptoms in 391(98.5%). Dysmenorrhea, premenstrual syndrome and heavy bleeding were significantly associated with stress level (p<0.05). Conclusion: Most students had heavy bleeding and dysmenorrhea, which were severe enough to require analgesics. There was a significant association between high stress levels and the occurrence of menstrual abnormalities Key Words: Dysmenorrhea, Menarche, Premenstrual, Stress, Psychological, Analgesics